Optimasi parameter model hujan-aliran mock dengan 'solver' - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT Lack of discharge data in a river basin is a major problem in water resources development in Indonesia. Hydrologic modelling such as rainfall-runoff models are used to overcome that problem. One of the rainfall-runoff model that widely used in Indonesia is Mock model. Application of Mock model, however, is not an easy task, especially in determining the parameters of the model. `Solver', one of fasilities in the Microsoft Excel, is applied to determine the optimal parameters of the Mock model. Results show that parameter optimisation of Mock model can be carried out relatively easy and it yields good performance.